Hydrological Services of Forests and Their Compensation Initiatives - Hendrayanto; Sudarsono Soedomo (Jurnal Manajemen Hutan Tropika, 2013)
Rapid decreas of natural forest, and more frequent disaster related to the roles of forest on precipitation, flood, drought, erosion, and sedimentation as well as landslides, biodiversity, and carbon sequestration have driven initiatives to find out economic instruments for raising incentives for better land rehabilitation and forest management. Payment or compensation for hydrological services of forest is one of economic instruments that was initiated to address water availability, flood and drought, erosion, and sedimentation issues. Hydrological services of forest to some extent are still debatable, and the magnitude of the services or influences of forest varies depending on the quality of forest cover and soil, climate, and physical characteristics of land. In most cases, payment or compensation schemes of forest services to the land owner or manager that have been implemented already, do not consider the actual forest hydrological services yet. Nevertheless, those payment schemes have been driving the activities of better land and forest uses, although they are still limited to small scales relative to the whole required area to produce forest hydrological services. This article reviews the hydrological services of forests and their compensation scheme developed in Indonesia.